2021
DOI: 10.1101/2021.12.05.471257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmentally-induced DNA methylation is inherited across generations in an aquatic keystone species (Daphnia magna)

Abstract: Environmental stress can result in epigenetic modifications that are passed down several generations. Such epigenetic inheritance can have significant impact on eco-evolutionary dynamics, but the phenomenon remains controversial in ecological model systems. Here, we used whole-genome bisulfite sequencing on individual water fleas (Daphnia magna) to assess whether environmentally-induced DNA methylation can persist for up to four generations. Genetically identical females were exposed to a control treatment, on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Whether these patterns are due to within-generation plastic responses associated with epigenetic changes or transgenerational inheritance of epigenetic factors, however, is often unclear, but compelling examples exist. In Polygonum plants, drought conditions led parents to produce offspring with longer roots, an adaptive phenotype that has been shown to be mediated by methylation (Herman & Sultan 2016); in stickleback fish, populations from marine environments with different salinities exhibit differences in methylation markers and laboratory experiments that vary salinity have shown that a subset of these same methylation differences are inducible and exhibit transgenerational plasticity, suggesting a role of adaptively inducible epigenetic variation in nature (Heckwolf et al 2020); in Daphnia, stress-induced epigenetic modifications occurred and persisted up to four generations, with modification occurring especially in stress-related genes, suggesting a possible role of heritable epigenetic change in adaptation (Feiner et al 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these patterns are due to within-generation plastic responses associated with epigenetic changes or transgenerational inheritance of epigenetic factors, however, is often unclear, but compelling examples exist. In Polygonum plants, drought conditions led parents to produce offspring with longer roots, an adaptive phenotype that has been shown to be mediated by methylation (Herman & Sultan 2016); in stickleback fish, populations from marine environments with different salinities exhibit differences in methylation markers and laboratory experiments that vary salinity have shown that a subset of these same methylation differences are inducible and exhibit transgenerational plasticity, suggesting a role of adaptively inducible epigenetic variation in nature (Heckwolf et al 2020); in Daphnia, stress-induced epigenetic modifications occurred and persisted up to four generations, with modification occurring especially in stress-related genes, suggesting a possible role of heritable epigenetic change in adaptation (Feiner et al 2021).…”
mentioning
confidence: 99%
“…2020); in Daphnia , stress‐induced epigenetic modifications occurred and persisted up to four generations, with modification occurring especially in stress‐related genes, suggesting a possible role of heritable epigenetic change in adaptation (Feiner et al. 2021).…”
mentioning
confidence: 99%
“…Theoretically, the environmental adaptation of the clonal animals described above and the establishment of epigenetic ecotypes could result from the repeated de novo production of identical, environmentally-induced phenotypes in each generation and/or the transgenerational inheritance and selection of adaptive epigenotypes. The example of the brain coral and recent reviews on the inheritance of epigenotypes (Jablonka, 2017;Anastasiadi et al, 2021;Feiner, 2021;Skinner & Nilsson, 2021) suggest that transgenerational epigenetic inheritance can play an important role in long-term adaptation of genetically uniform populations to different environments, indeed. Final answering of this question requires cross-transplantation experiments and monitoring of epigenetic fingerprints for dozens of generations, which have not been done as yet.…”
Section: Ecological Implications Of Epigenetic Phenotypes and Ecotypesmentioning
confidence: 99%